2018
DOI: 10.1111/eva.12650
|View full text |Cite
|
Sign up to set email alerts
|

Human activities and landscape features interact to closely define the distribution and dispersal of an urban commensal

Abstract: The rock pigeon, Columba livia, is a cosmopolitan human commensal, domesticated thousands of years ago. However, the human‐mediated factors governing its distribution and dispersal are not well understood. In this study, we performed (a) hierarchical distance sampling on ~400 island‐wide point transects, (b) a population genomic inquiry based on ~7,000 SNPs from almost 150 individuals, and (c) landscape genomic analyses on the basis of extensive ecological and socio‐economic databases to characterize the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…As M. m. domesticus was probably introduced in Australia by European settlers in the late 18 th Century, the absence of mutations in the exons of VKORC1 might because they were absent from these founder animals [35,36]. The mitochondrial D-loop data supports this, as the low haplotype diversity indicates rapid expansion from a small founding population [37]. ARs were invented in the 1940s, and the first evidence of resistance in rodents dates to 1958 [18].…”
Section: Plos Onementioning
confidence: 87%
“…As M. m. domesticus was probably introduced in Australia by European settlers in the late 18 th Century, the absence of mutations in the exons of VKORC1 might because they were absent from these founder animals [35,36]. The mitochondrial D-loop data supports this, as the low haplotype diversity indicates rapid expansion from a small founding population [37]. ARs were invented in the 1940s, and the first evidence of resistance in rodents dates to 1958 [18].…”
Section: Plos Onementioning
confidence: 87%
“…Our ResDisMapper results on the pigeons in Singapore indicate high resistance to dispersal in central and western Singapore, which mainly comprise nonfavourable habitats for the rock pigeons such as dense trees and industrial zones. Compared to the mapping of resistance to dispersal in the original study (Tang et al, ) using DResD , the resistance mapping from ResDisMapper is more congruent with the landscape patterns in Singapore (Figure and Figure S4). Congruence between mapped resistance and landscape pattern is found regardless of whether resistance was calculated using sample pairs of individuals within 5, 10, 15, 20, 25 or 30 km (Figure S4).…”
Section: Resultsmentioning
confidence: 80%
“…This effect is best corrected by including only those sampled pairs within the typical range of dispersal. According to a previous spatial autocorrelation analysis, the typical range of dispersal for pigeons in Singapore was estimated to be within 10 km (Tang et al, ). Accordingly, the resistance map derived using only sampled pairs within 10 km should be the most relevant for illustrating the resistance to dispersal of pigeons in Singapore, and indeed, we found that this map was most congruent with what we expected from the landscape pattern (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of the above-mentioned 73 studies on domestic breeds actually included one group of feral pigeons in their analyses (e.g. 74 Stringham et al 2012;Biala et al 2015), only two studies were specifically focused on feral 75 pigeons, with the aim of clarifying the pattern of genetic differentiation within and between urban 76 areas (Jacob et al 2015;Tang et al 2018). To our knowledge, no study has systematically 77 investigated the degree of influence of different domestic breeds on the genetic composition of feral 78 populations.…”
mentioning
confidence: 99%